2021
DOI: 10.1093/mnras/stab3504
|View full text |Cite
|
Sign up to set email alerts
|

The GALAH Survey: chemical tagging and chrono-chemodynamics of accreted halo stars with GALAH+ DR3 andGaiaeDR3

Abstract: Since the advent of Gaia astrometry, it is possible to identify massive accreted systems within the Galaxy through their unique dynamical signatures. One such system, Gaia-Sausage-Enceladus (GSE), appears to be an early “building block” given its virial mass >1010 M⊙ at infall (z ∼ 1 − 3). In order to separate the progenitor population from the background stars, we investigate its chemical properties with up to 30 element abundances from the GALAH+ Survey Data Release 3 (DR3). To inform our choice of el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 196 publications
(368 reference statements)
10
44
0
Order By: Relevance
“…The angular momentum restriction ensures we are not including stars on more prograde/retrograde orbits. We find that by selecting the GES substructure in this manner, we obtain a sample of stars with highly radial (J 𝑅 ∼1x10 3 kpc kms −1 ) and therefore highly eccentric (𝑒∼0.9) orbits, in agreement with selections employed in previous studies to identify this halo substructure (e.g., Mackereth & Bovy 2020;Naidu et al 2020;Feuillet et al 2021;Buder et al 2022). The final GES sample is comprised of 2,353 stars.…”
Section: Gaia-enceladus/sausagesupporting
confidence: 81%
See 1 more Smart Citation
“…The angular momentum restriction ensures we are not including stars on more prograde/retrograde orbits. We find that by selecting the GES substructure in this manner, we obtain a sample of stars with highly radial (J 𝑅 ∼1x10 3 kpc kms −1 ) and therefore highly eccentric (𝑒∼0.9) orbits, in agreement with selections employed in previous studies to identify this halo substructure (e.g., Mackereth & Bovy 2020;Naidu et al 2020;Feuillet et al 2021;Buder et al 2022). The final GES sample is comprised of 2,353 stars.…”
Section: Gaia-enceladus/sausagesupporting
confidence: 81%
“…Sagittarius dSph, Ibata et al 1994;Helmi stream, Helmi et al 1999), the identification of accretion events early in the life of the Milky Way has proven difficult due to phase-mixing. A possible solution to this conundrum resides in the use of additional information, typically in the form of detailed chemistry and/or ages (e.g., Nissen & Schuster 2010;Hawkins et al 2015;Hayes et al 2018;Haywood et al 2018;Mackereth et al 2019;Das et al 2020;Montalbán et al 2020;Horta et al 2021a;Hasselquist et al 2021;Buder et al 2022;Carrillo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The accreted component in FB20 D2 has a mean net zero rotational velocity, similarly to what is measured for the GSE (e.g. Belokurov et al 2018;Helmi et al 2018;Buder et al 2022), but model FB80 D2, which has the same satellite orbit, shows a slight retrograde net motion. This is also the case for models with dwarf D1, with the stronger feedback leading to the most retrograde realisation of the GSE.…”
Section: The Accreted Starssupporting
confidence: 59%
“…This is especially promising as Das et al (2020) showed that using this combination of abundances, their sample of accreted stars have older ages (see their Figure 7) and kinematics (see their Figure 8) similar to accreted stars in the literature (e.g., Belokurov et al 2018). Whether selecting dynamically or chemically gives a cleaner or different sample of accreted stars is worth exploring and has been the subject of the work from Buder et al (2022). Using GALAH DR3 data and the combination of [Na/Fe] and [Mg/Mn], the authors found that their GES sample from a chemical selection overlaps with 29% of a pure dynamicallyselected sample, as suggested by Feuillet et al (2021).…”
Section: Accreted Stars Selectionmentioning
confidence: 92%